The effects of medium-oil dried distillers grains with solubles on growth performance and carcass traits in finishing pigs - A B Graham; S Nitikanchana; Robert D Goodband; Michael D Tokach; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
An experiment was conducted to determine the effects of increasing medium-oil dried distillers grains with solubles (DDGS; 7.4% fat, 28.1% CP, 10.8% ADF, and 25.6% NDF) on growth performance and carcass traits in finishing pigs. A total of 288 pigs (PIC 327 × 1050; initially 151.8 lb) were allotted to 1 of 4 dietary treatments. Treatments consisted of a corn-soybean meal control diet or the control diet with 15, 30, or 45% medium-oil DDGS, with 8 pigs per pen and 8 replications per treatment. Increasing medium-oil DDGS decreased (linear, P<0.01) ADG and worsened (linear, P<0.02) F/G. In addition, final BW, HCW, carcass yield, and loin-eye depth decreased (linear, P<0.03), and jowl iodine value (IV) increased (linear, P<0.001) with increasing medium-oil DDGS. When pigs are fed traditional DDGS containing>10.5% fat, each 10% DDGS added to the diet increases jowl IV approximately 2 mg/g; however, feeding increasing medium-oil DDGS increased jowl IV only about 1.4 units per each 10% DDGS. In conclusion, swine producers must be aware of the negative ramifications on growth performance of using medium-oil DDGS in swine diets.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; DDGS; Finishing pig; Iodine value; Medium-oil DDGS